(untitled) (Englisia : Journal of Language, Education, and Humanities, 2023)
This study delved into the impact of the E-learning crack-up on the learning process during the pandemic to the post-pandemic learning process and the quality of English learning during face-to-face learning. This study applied qualitative research methods. The researchers selected six students from class XI-1 and one teacher at SMAN 1 Nunukan to participate in the interview session. In the data collection process, documents, observations, and interviews as research instruments were implemented. The researchers analyzed research data through three phases: data condensation, presentation, and conclusion verification. From the data analysis, the researchers found that E-learning crack-ups in the learning process during the pandemic affected students’ learning processes. This is evidenced by the results of student interviews, which stated that they were still trying to adapt to the learning process in the post-pandemic period. However, based on the observations and document reviews, the researchers also found that the students’ adaptation process during the post-pandemic learning period was excellent because it was supported by an exciting learning process and the implementation of Kurikulum Merdeka at Nunukan 1 Public High School. Thus, the quality of learning at SMAN 1 Nunukan is outstanding.